Analysis of seroprevalence and risk factors for syphilis and HIV among female sex workers and transgender individuals in different cities of Sindh, Pakistan - Sharaf A. Shah; Maria Zubair; Altaf Soomro; Rasheed Sheikh; Alnara Zhamalbekova; Syed Hani Abidi (PLoS ONE, 2025)
Introduction Co-infections of syphilis and HIV have been found to exacerbate the impact on sexual and reproductive health, especially among key population groups such as Female Sex Workers (FSWs) and Transgender Individuals (TGs). The data on the prevalence and determinants of syphilis and HIV in Pakistan, particularly in Sindh province, is limited. This prospective cross-sectional study aimed to determine the seroprevalence and risk factors for HIV and syphilis infections among FSWs and TGs in different cities of Sindh, Pakistan. Methods A total of 1120 participants (531 FSWs and 589 TGs) were recruited from Karachi, Sukkur, Hyderabad, and Larkana. Community-based serological testing for HIV and syphilis was performed using Abbot Bioline HIV/syphilis Duo test kits, and sociodemographic and risk factor data were collected through questionnaires. Chi-square and logic regression were applied to determine variables associated significantly with syphilis in TGs and FSWs. Results TGs exhibited higher rates of syphilis (16.29%) and syphilis-HIV (6.79%) as compared to FSWs (syphilis: 15.63%; syphilis-HIV: 0.75%). Inconsistent condom use was more common among FSWs (75.32%), and over half reported STI symptoms. Regression analysis showed that for TGs, having five years (adjusted OR: 0.52, p = 0.04) and graduate-level education (adjusted OR: 0.40, p = 0.04) was associated with a lower risk of syphilis, while an income between 30,000 and 50,000 Pakistani rupees (OR: 1.93, p = 0.028) and more than three years in profession (adjusted OR: 2.20, p = 0.04) was associated with a higher risk. For FSWs, five (OR: 0.34, p = 0.03) and ten (OR: 0.02, p = 0.02) years of education were associated with a lower risk of syphilis, whereas an income between 30,000 and 50,000 PKR (OR: 3.05, p < 0.01) and self-reported HIV-negative status (OR: 3.08, p = 0.01) were associated with a higher risk of syphilis mono-infection. Conclusion In conclusion, the results of the study show higher rates of syphilis and HIV co-infection among TG compared to FSW from Sind. The study findings provide valuable insights for national health agencies and policymakers to devise data-driven strategies for preventing and controlling syphilis and HIV infections among FSW and TG populations in Sind.